Impact of different anesthetics on ischemia reperfusion injuries in patients undergoing hepatectomy: a network meta-analysis - Wang, Shaojuan; Tian, Fangyuan; Zhang, Rui; Deng, Zehui; Zhou, Ling; Ren, Lin; Wu, Fengbo (Frontiers in Medicine, 2026)
BackgroundHepatectomy, a commonly employed surgical approach for treating liver-related disorders, has emerged as the primary method for the radical treatment of early stage liver cancer. This network meta-analysis was conducted to evaluate the impacts of different anesthetics on ischemia reperfusion injuries in patients undergoing hepatectomy.MethodsRandomized controlled trials (RCTs) and cohort studies were identified through searches in four databases, PubMed, Embase, the Cochrane Library, and the Web of Science, up to February 12, 2025. Non-English studies were excluded, and this study was conducted in compliance with PRISMA-NMA guidelines. Bayesian network meta-analysis was employed based on the R 4.3.2 and Stata 15.1. The efficacy of each intervention was evaluated through SUCRA (surface under the cumulative ranking curve).ResultsThe analysis included 19 studies with a total of 1,319 participants. In terms of reducing aspartate transaminase (AST) levels, the combination of propofol and sevoflurane exhibited the highest effectiveness (SUCRAs: 71.82%), followed by the combination of propofol, isoflurane, and fentanyl (SUCRAs: 61.87%), and sevoflurane monotherapy (SUCRAs: 58.61%). The combination of propofol and sevoflurane (SUCRAs: 71.94%) ranked first for reducing ALT levels, followed by propofol monotherapy (SUCRAs: 61.71%) and the combination of propofol and sufentanil (SUCRAs: 58.59%).ConclusionThe combination of propofol and sevoflurane appear to be the most effective approach for reducing AST and ALT levels. This combination could serve as a favorable anesthetic strategy to limit hepatic enzyme elevations after hepatectomy, thus supporting liver function protection.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/home, identifier CRD42023472070.